Prevalence of ATD (Anti Tuberculosis Drugs) Hypersensitivity Reactions in HIV Patients Period 2021 at Sanglah Central General Hospital - Roykhan Prayudianto (Rifa'Institute, 2022)
Introduction: Tuberculosis is a disease caused by Mycobacterium tuberculosis. Pulmonary tuberculosis (pulmonary TB) is tuberculosis that attacks the lung tissue (parenchyma) excluding the pleura (lung membrane) and glands in the hilum, which has a wide spectrum of clinical manifestations ranging from asymptomatic infection to severe respiratory symptoms and even death. Tuberculosis an important cause of death among patients infected with HIV. Method: This study is a descriptive study with cross-sectional approach. Sampling with consecutive sampling. This sampling was done from January 2021 until December 2021. Analysis done with SPSS application. Results: From 25 patients with HIV and hypersensitivity TB drugs, we found 72% was male vs 28% was female, 80% patients with Pre HAART vs 20% with on HAART. There is show has not associate with the severity of HIV. Conclusion: From this study, we can learn the hypersensitivity patients do not associate with severity of HIV. However, this study has a lot of weakness from methods, analysis and sample similarity. We hope that another study can be better method than this study.